Teaching Styles of Mosston and Arshworth: From the Origin to Nowadays (2022)
This review is part of the systematization of experiences in teaching styles (TS) for basic motor skills in Physical Education (PE) and aims to collect and analyze recent research based on the TS spectrum with the purpose of identifying the application that is being given to this theory in the field of Physical Education today. There are several classification proposals for TS in PE. However, even though four decades have passed, since its formulation in 1993, Mosston and Arsworth's theory is still in force, serving as a theoretical basis for the study of the didactics of PE. A documentary analysis and review (DAR) was carried out, for which the keywords were used: teaching styles, Physical Education, and teaching. The documents were filtered for their relevance and quality in Research Gate, Redalyc, Dialnet, PubMed and Semantic Scholar, and the heuristic phase was completed by carrying out the hermeneutical process with 23 documents found related to TS and PE from the perspective of Mosston and Arshworth, identifying that there is evidence of a greater investigation in reproductive TS compared to productive ones. In the same way, a general trend towards the implementation of reproductive TS is demonstrated despite finding important benefits provided by productive TS. As conclusions, it is identified that the effectiveness of implemented TS depends on the application context. Likewise, the need to implement research related to productive TS is reinforced which makes it possible to highlight the great benefits of these strategies. Finally, the permanent inclusion of the theory of Mosston and Arshworth in different investigations, confirms the importance of such classification when addressing issues related to TS in PE.